PENINGKATAN PRODUKSI TANAMAN KACANG TANAH MELALUI PEMBERIAN PUPUK ORGANIK - Eny Hari Widowati; Bistok Hasiholan; Sriyanto Sriyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Peanut (Arachys hypogaea L.) is one of the highly nutritious foods. Every 100 grams contains calories 583 kcal, protein 23 grams, cholesterol 0%, 23 grams carbohydrate, 8 grams fiber, 22 grams phytosterol, beta - phytosterol 6.5 grams. The ain of the research: (1) Agrotecnology adaptation test of organic fertilizer to increase productivity. (2) To determine ideals dose of organic and anorganic fertilizer (3) To analyze aflatoxsin stimulation, The location of the research was Jepara Regency has good land characteristic for peanuts growt, The result of the research, are: (1) The use of organic fertilizer compottion with 1000 kg.ha¹ and anorganic fertilizer with nitrogen 50 kg.ha¹, phosphate 60 kg.ha-1 and 100 kg kalium.ha-1 ( pattern C) produces the characteristic chemical, physical and biology the best land. (2) Other treatment (pattern A, B, D and E) gives the results of chemical, physical and biology of the diverse land. (3) Treatment C give performances of the highest value, of: (a) Weight of dry seed in 1000 seeds weighing 307.53 grams (an increase of 34.86% of control), (b) Dry seed weight of 2.30 tonnes per ha. ( c) full of pods containing 78.89% (increase. 8.20%% of control), (d) production performance in terms of economic aspects of quality, namely the yield, the loop product, the highest yield in treatment D, 82, 03% or an increase of 40.95% of the control loop on the product yield as much as 58.20%. The product of pods, the highest yield in treatment E (organic fertilizer 2,000 kg / ha) of 81.94% or an increase of 41.18% of production pod control treatment as big as 58.04%. (3) Content of aflatoxin is influenced by the varieties of plants (genetic) and environment, especially soil and climate both on land and in the process of post-harvest. In treatment C, the lower aflatoxin content were both of seed after harvest (<1 ppb) and after storage for 1 month (30 days). Treatment C is economically provide the highest profits. The results can not be used farmers, because the test is done once the new adaptation. Stability of production and nutrients in each treatment is not optimal. So still need further study to achieve production stability and nutrients in the soil with the same experimental design at least 3 (three) times the investment. In addition, it is necessary also varieties that are resistant to postharvest infection of Aspergillus, sp appropriate to reduce the negative effect of aflatoxin.